2020
DOI: 10.22271/chemi.2020.v8.i3b.9218
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical analysis of soils in Madanapalle block, Chittor district of Andhra Pradesh

Abstract: Soil is a mixture of minerals, gases, liquids and organisms that together forms the basis of life. The inherent capacity of soil to provide essential nutrients to crops describes the soil in terms of fertility. In the present study physico-chemical analysis of soils in Madanapalle town was analysed by selecting eight different villages and from each village 3 surface (0-15cm) soil samples were collected and analysed for physical and chemical parameters by using standard laboratory techniques. Accordingly it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The findings showed that as soil particles erode, they fill up the pore spaces, raising the bulk density of the soil and decreasing its porosity. Srinidhi et al (2020) recorded similar observations in the Chittoor district of Andhra Pradesh. The overall distribution of bulk density, particle density, and porosity is presented in Figure 7, 8, and 9.…”
Section: Bulk Density Particle Density and Porosity Distributionsupporting
confidence: 65%
“…The findings showed that as soil particles erode, they fill up the pore spaces, raising the bulk density of the soil and decreasing its porosity. Srinidhi et al (2020) recorded similar observations in the Chittoor district of Andhra Pradesh. The overall distribution of bulk density, particle density, and porosity is presented in Figure 7, 8, and 9.…”
Section: Bulk Density Particle Density and Porosity Distributionsupporting
confidence: 65%